A qualitative study on clinical research in Finland: fragmented governance and volume in the 2000s. Issue 2 (13th February 2013) - Hemminki, Elina; Veerus, Piret; Virtanen, Jorma; Lehto, Juhani
Abstract : Objectives: Although concerns over clinical research have been expressed, the governance of clinical research has been little studied. The aim was to describe research policy, volume, funding and concerns over clinical research in Finland. Design: A qualitative study and the data were collected from various sources, including documents, statistics and semistructured expert interviews. Setting: Finland. Results: We found no national policy for clinical research. Many actors were responsible for facilitating, directing, regulating and funding clinical research, but no actor had the main responsibility. Health professionals were the main drivers for clinical research. The role of the health ministry was small. The ministry distributed state money for clinical research in health services (EVO-money), but did not use it to direct research. Municipalities responsible for health services or national health insurance had little interest in clinical research. The Academy of Finland had had initiatives to promote clinical research, but they had not materialised in funding. Clinical research was common and internationally competitive, but its volume had declined relatively in the 2000s. Industry was an important private funder, mainly supporting drug trials made for licensing purposes. Drug trials without an outside sponsor (academic projects) declined between 2002 and 2010. The funding and its targeting and amount were no one's responsibility. Concerns over clinical research were similar as in other countries, but it had appeared late. Conclusions: Our results suggest fragmented governance and funding in clinical research. The unsystematic research environment has not prevented clinical research from flourishing, but the public health relevance of the research carried out and its sustainability are unclear.